The Illocutionary Acts in X Social Media Platform: “Hold On, It Hurts,” an Indonesian Alternative Universe (AU) by Noveni Adelia (e-Journal of Linguistics, 2024)
This article explores illocutionary acts within the "Hold On, It Hurts" Alternative Universe (AU) in the X application, utilizing Yule's theoretical framework as its foundation. The study focuses on how language, specifically illocutionary acts, creates and conveys meaning in this unique digital narrative space. Yule's theory also defines the classifications of speech acts, such as representative, directive, commissive, expressive, and declarative, and serves as a lens to dissect and understand the intricacies of communication within the AU. The research primarily centers on the illocutionary acts, examining how the characters in the "Hold On, It Hurts" AU use language not just for literal communication but to perform various actions and express complex emotions. The study investigates the dynamics between the speaker and listener within the AU, highlighting how context, speaker intentions, and underlying emotional states are crucial in interpreting these acts.
Keywords: AU; X; Twitter; Illocutionary; Acts